Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery

By preparation of lithium iron phosphate positive materials, the method of mixing and organic acid regulation of different iron phosphorus ratio is used to solve the problem of low compact density and poor discharge performance of lithium iron phosphate. Press density and discharge performance.

CN119370818AActive Publication Date: 2025-01-28HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411498700.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing lithium iron phosphate positive electrode materials have low compaction density and poor discharge performance, which limits their application performance in lithium-ion batteries.

Method used

By formulating two kinds of slurry with different iron phosphorus ratio in parallel, and mixing it for hydrophilic reactions, combined with the introduction of organic acid in the solvent system, regulating the appearance and crystal structure of lithium iron phosphate, forming a high exposure of 010 crystal surface Material.

Benefits of technology

It significantly improves the compact density and discharge performance of lithium iron phosphate, and improves its service life and electrochemical properties in lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370818A_ABST
    Figure CN119370818A_ABST
Patent Text Reader

Abstract

The invention provides a lithium iron phosphate positive electrode material, a preparation method thereof and a lithium ion battery. The preparation method comprises the following steps: preparing a first slurry from a first phosphorus source, a first iron source, a first carbon source, a first lithium source and a first solvent; preparing a second slurry from a second phosphorus source, a second iron source, a second carbon source, a second lithium source and a second solvent; and mixing the first slurry and the second slurry to obtain third slurry, and reacting and drying the third slurry to obtain the lithium iron phosphate positive electrode material, in the first slurry, the molar ratio of the P element to the Fe element to the Li element is N1; in the second slurry, the molar ratio of the P element to the Fe element to the Li element is N2; n1 is not equal to N2; the first solvent and the second solvent both comprise water, ethylene glycol and organic acid. According to the invention, reaction systems with different iron-phosphorus ratios are constructed, and the organic acid is introduced into a solvent system of the reaction, so that the lithium iron phosphate positive electrode material with higher compaction density and better discharge performance is finally prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a lithium iron phosphate positive electrode material, a preparation method thereof and a lithium ion battery. Background Art

[0002] Lithium iron phosphate (LiFePO 4 ), is an important cathode material for lithium-ion batteries, and occupies an important position in the field of energy storage with its unique advantages. Lithium iron phosphate was first discovered by Professor John B. Goodenough's team at the University of Texas at Austin in 1997, and was quickly applied to lithium-ion batteries due to its excellent electrochemical properties. Lithium iron phosphate has a high theoretical specific capacity (about 170 mAh / g), stable electrochemical properties, and good cycle stability. Compared with other cathode materials, lithium iron phosphate has better thermal stability and lower risk of thermal runaway, which gives it an advantage in safety.

[0003] However, despite its many advantages, lithium iron phosphate still faces challenges that make it difficult to apply on a large scale, including low theoretical energy density and conductivity. In order to overcome these limitations, researchers in this field are developing new synthesis methods, nanostructure design and composite material preparation to continuously explore ways to improve its performance, including improving its energy density, power density and cycle life through doping, surface modification, structural optimization and other means.

[0004] Among the many physical and chemical characteristics of lithium iron phosphate positive electrode materials, compaction density and powder resistivity are important indicators that affect their application performance in lithium-ion batteries. Among them, compaction density refers to the mass of a unit volume of positive electrode material under a certain pressure. The greater the compaction density, the less positive electrode material is used per unit volume. Powder resistivity refers to the resistance of the positive electrode material in a powder state. The greater the powder resistivity, the greater the resistance to electron and ion transmission on the surface and inside of the positive electrode material, and the lower the battery's charge and discharge efficiency. Therefore, increasing the compaction density of lithium iron phosphate positive electrode materials and reducing their powder resistivity will help improve the application performance of lithium iron phosphate positive electrode materials in lithium-ion batteries.

[0005] Based on this, how to optimize the preparation method of lithium iron phosphate positive electrode material so that the obtained lithium iron phosphate has a higher compaction density and better discharge performance is one of the important technical problems that need to be solved in this field. Summary of the invention

[0006] The main purpose of the present invention is to provide a lithium iron phosphate positive electrode material, a preparation method thereof and a lithium ion battery, so as to solve the problems of low compaction density and poor discharge performance of the lithium iron phosphate positive electrode material in the prior art.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a method for preparing a lithium iron phosphate positive electrode material, comprising: step S1, preparing a first phosphorus source, a first iron source, a first carbon source, a first lithium source and a first solvent into a first slurry; step S2, preparing a second phosphorus source, a second iron source, a second carbon source, a second lithium source and a second solvent into a second slurry; step S3, mixing the first slurry with the second slurry to obtain a third slurry, and obtaining a lithium iron phosphate positive electrode material after the third slurry is reacted and dried; in the first slurry, the molar ratio of the P element, the Fe element and the Li element is N1; in the second slurry, the molar ratio of the P element, the Fe element and the Li element is N2; N1 and N2 are not equal; the first solvent and the second solvent both include water, ethylene glycol and an organic acid.

[0008] In the above-mentioned preparation method provided by the present invention, firstly, two slurries with different iron-phosphorus ratios are prepared in parallel during the raw material mixing process, and then the two are mixed, and the effect of coordination between large and small particles is achieved after hydrothermal reaction. The slurry system with a low iron-phosphorus ratio provides lithium iron phosphate with larger primary particles, and the slurry system with a high iron-phosphorus ratio provides lithium iron phosphate with smaller primary particles. The lithium iron phosphate prepared by mixing the two and reacting them has a more uniform particle size distribution, a greatly improved compacted density of the obtained material, a significantly reduced resistivity, and an increased gram capacity. At the same time, with respect to the solvent system, i.e., the first solvent and the second solvent, the present invention creatively introduces an organic acid therein, thereby regulating the morphology and crystal structure of the prepared lithium iron phosphate, inducing a lithium iron phosphate material with a high exposure of the 010 crystal plane, and significantly improving the long-range order of the crystal of the generated lithium iron phosphate material, reducing its internal defects, and then improving the conductivity of the obtained lithium iron phosphate material, so that its discharge gram capacity is significantly improved, and the electrochemical performance is more superior. The lithium iron phosphate material prepared by the above-mentioned preparation method provided by the present invention has a higher degree of order in its crystal structure, which is further manifested in that the material has higher stability and is less likely to decompose when subjected to heat or other energy shocks. Therefore, when it is used as a positive electrode material and prepared into a lithium-ion battery, its service life is longer, and its corresponding lithium-ion battery electrical performance is also higher.

[0009] Furthermore, in the first slurry, N1 is (0.9-1.0):1:(1.5-3.0); in the second slurry, N2 is (1.0-1.2):1:(1.5-3.0). The adjustment of the above molar ratio range is more conducive to the formation of lithium iron phosphate with larger primary particles in the slurry system with a low iron-phosphorus ratio, and the formation of lithium iron phosphate with smaller primary particles in the slurry system with a high iron-phosphorus ratio. This allows the precursor particle size distribution provided by the two slurry systems to be better coordinated, forming a lithium iron phosphate positive electrode material with a more stable lattice structure and a more suitable particle size distribution, and ultimately improving the compaction density and discharge performance of the resulting material.

[0010] Furthermore, in the first solvent and the second solvent, the weight ratio of water, ethylene glycol and organic acid is independently (1.0-2.0): (0.5-1.0): (1.0-3.0); preferably, the organic acid is selected from one or more of malonic acid, succinic acid, citric acid and oxalic acid. The solvent prepared by mixing water, ethylene glycol and organic acid in the above weight ratio can improve the rheological properties of the slurry while more significantly exerting the regulating and inducing effect of organic acid on the crystal structure, promote the uniform dispersion and growth of the obtained positive electrode material particles, thereby obtaining a denser and more compacted lithium iron phosphate material. The above-mentioned types of organic acids can not only be used as inducers to optimize and regulate the crystal structure of lithium iron phosphate positive electrode materials, but also can be better compatible with P elements, Fe elements and Li elements, optimize the crystal growth rate and morphology during the reaction process, thereby obtaining lithium iron phosphate positive electrode materials with better electrochemical properties.

[0011] Further, step S1 also includes adding a first pH regulator to the first slurry so that the pH of the first slurry is 6.5 to 7.5 to obtain a first precursor; step S2 also includes adding a second pH regulator to the second slurry so that the pH of the second slurry is 6.5 to 7.5 to obtain a second precursor; preferably, the first pH regulator and the second pH regulator are independently selected from one or more of hydrochloric acid, sulfuric acid, malonic acid, succinic acid, citric acid and oxalic acid. By adjusting the pH value of the two slurries, the precipitation conditions of the precursors can be optimized, and two precursors with different particle size distributions can be obtained in advance, thereby more effectively optimizing the particle size distribution of the final lithium iron phosphate positive electrode material in the subsequent mixing and reaction process, improving the purity and crystallinity of the material, and making it exhibit higher electrochemical performance. The selection of the above-mentioned pH regulator can not only effectively control the acidity and alkalinity of the first slurry and the second slurry, but also more effectively promote the formation of two precursors with different particle size distributions, thereby improving the electrochemical activity of the final positive electrode material.

[0012] Furthermore, in step S3, the weight ratio of the first precursor in the first slurry to the second precursor in the second slurry is (5-10): 1. Such ratio control can better coordinate the two precursors with different particle sizes and distributions, improve the uniformity during the reaction, better avoid crystal defects, and ultimately make the compaction density and discharge performance of the obtained lithium iron phosphate cathode material higher.

[0013] Further, based on the total weight of the first phosphorus source, the first iron source, the first carbon source and the first lithium source as 100%, the addition amount of the first carbon source accounts for 0.5% to 1.5%; and / or, based on the total weight of the second phosphorus source, the second iron source, the second carbon source and the second lithium source as 100%, the addition amount of the second carbon source accounts for 0.5% to 1.5%; preferably, the weight ratio of the total weight of the first phosphorus source, the first iron source, the first carbon source and the first lithium source to the first solvent is (10 to 20): (1 to 5); and / or, the weight ratio of the total weight of the second phosphorus source, the second iron source, the second carbon source and the second lithium source to the second solvent is (10 to 20): (1 to 5). The introduction of the above-mentioned specific addition amount of the carbon source can form a more uniform carbon coating layer, thereby further improving the conductivity of the obtained positive electrode material, reducing its internal resistance, and making it exhibit a lower resistivity. In order to promote the precursor generation reaction and the subsequent reaction of obtaining the positive electrode material to proceed more fully, while also improving the dispersion uniformity of the reaction system at each stage, and better reducing the adverse effects of solvent residue on material properties, the addition amount of the above solvent is preferably selected.

[0014] Furthermore, the first phosphorus source and the second phosphorus source are each independently selected from phytic acid, NH 4 H 2 PO 4 and phosphoric acid; and / or, the first iron source and the second iron source are each independently selected from FeSO 4 7H 2 O、FePO 4 and Fe 2 O 3 One or more of; and / or, the first lithium source and the second lithium source are each independently selected from LiOH·H 2 O. Li 2 CO 3 and CH 3 COOLi; and / or, the first carbon source and the second carbon source are independently selected from one or more of glucose, sucrose and polyethylene glycol. The selection of the above raw material types can not only meet the synthesis requirements of lithium iron phosphate positive electrode materials, but more importantly, it can more effectively promote the optimization of material particle size distribution according to the preparation method provided by the present invention, thereby improving its compaction density and discharge performance.

[0015] Furthermore, the reaction temperature is 150°C to 300°C, and the reaction time is 2h to 6h; the drying temperature is 60°C to 120°C, and the reaction time is 10h to 24h; preferably, the drying is vacuum drying. Under these reaction conditions, lithium iron phosphate with higher crystallinity, fewer defects, more stable structure and longer-range order is obtained, and its discharge performance is more superior. Control of drying conditions can more effectively remove residual moisture in the crystal structure of the obtained positive electrode material, and at the same time can more effectively protect the integrity, continuity and stability of the structure, so that it exhibits better electrochemical performance in lithium-ion batteries.

[0016] The second aspect of the present invention provides a lithium iron phosphate positive electrode material, which is prepared by the above-mentioned preparation method of the lithium iron phosphate positive electrode material, and the compaction density of the lithium iron phosphate positive electrode material is 2.50g / cm 2 ~2.72g / cm 2 , the powder resistivity is 3.5Ω·cm~9.5Ω·cm. The positive electrode material prepared by the present invention has higher compaction density and lower resistivity, and the crystal structure has higher long-range order, higher structural stability and higher service life.

[0017] The third aspect of the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive current collector and a positive active layer disposed on at least one side of the positive current collector, wherein the positive active layer comprises the above-mentioned lithium iron phosphate positive electrode material. Since the above-mentioned lithium iron phosphate obtained by the present invention has a higher compaction density, a lower powder resistivity and a more stable and long-range ordered crystal structure, when it is used as a positive electrode material in a lithium-ion battery, the obtained lithium-ion battery also exhibits higher electrical performance accordingly.

[0018] By applying the technical solution of the present invention, by constructing a reaction system with different iron-phosphorus ratios, particles with different particle size distributions can be obtained through a mixing reaction, thereby increasing the compaction density of the obtained material. At the same time, an organic acid is introduced into the solvent system of the reaction, thereby obtaining a lithium iron phosphate material with a superior crystal form, and ultimately preparing a lithium iron phosphate positive electrode material with higher compaction density and better discharge performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0020] Figure 1 0~2000cm -1 Within the range, the Raman spectrum curve of the lithium iron phosphate positive electrode material obtained in Example 1;

[0021] Figure 2 920cm -1 ~980cm -1 Within the range, the Raman spectrum curve of the lithium iron phosphate positive electrode material obtained in Example 1;

[0022] Figure 3 0~2000cm -1 In the range, the Raman spectrum curve of the lithium iron phosphate positive electrode material obtained in Comparative Example 1;

[0023] Figure 4 920cm -1 ~980cm -1 Within the range, the Raman spectrum curve of the lithium iron phosphate positive electrode material obtained in Comparative Example 1. DETAILED DESCRIPTION

[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0025] As described in the background technology, the lithium iron phosphate positive electrode material in the prior art has the problem of low compaction density and poor discharge performance. In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a lithium iron phosphate positive electrode material, comprising: step S1, preparing a first phosphorus source, a first iron source, a first carbon source, a first lithium source and a first solvent into a first slurry; step S2, preparing a second phosphorus source, a second iron source, a second carbon source, a second lithium source and a second solvent into a second slurry; step S3, mixing the first slurry with the second slurry to obtain a third slurry, and the third slurry is reacted and dried to obtain a lithium iron phosphate positive electrode material; in the first slurry, the molar ratio of the P element, the Fe element and the Li element is N1; in the second slurry, the molar ratio of the P element, the Fe element and the Li element is N2; N1 and N2 are not equal; the first solvent and the second solvent both include water, ethylene glycol and an organic acid.

[0026] In the above-mentioned preparation method provided by the present invention, two slurries with different iron-phosphorus ratios are first prepared in parallel during the raw material mixing process, and then the two are mixed, and the effect of coordinated matching of large and small particles is achieved after hydrothermal reaction. The slurry system with a low iron-phosphorus ratio provides lithium iron phosphate with larger primary particles, and the slurry system with a high iron-phosphorus ratio provides lithium iron phosphate with smaller primary particles. The lithium iron phosphate prepared by mixing the two and reacting them has a more uniform particle size distribution, and the compacted density of the obtained material is greatly improved, the resistivity is significantly reduced, and the gram capacity is increased.

[0027] At the same time, with respect to the solvent system, i.e., the first solvent and the second solvent, the present invention creatively introduces an organic acid therein, thereby regulating the morphology and crystal structure of the prepared lithium iron phosphate, inducing a lithium iron phosphate material with a highly exposed 010 crystal plane, and significantly improving the long-range order of the crystal of the generated lithium iron phosphate material, reducing its internal defects, and thereby improving the conductivity of the obtained lithium iron phosphate material, so that its discharge capacity is significantly improved, and its electrochemical performance is more superior.

[0028] It is worth mentioning that the lithium iron phosphate material prepared by the above-mentioned preparation method provided by the present invention has a higher degree of order in its crystal structure, which is further manifested in that the material has higher stability and is less likely to decompose when subjected to heat or other energy shocks. Therefore, when it is used as a positive electrode material and prepared into a lithium-ion battery, its service life is longer, and its corresponding lithium-ion battery electrical performance is also higher.

[0029] In several typical implementations, in the first slurry, N1 is (0.9-1.0):1:(1.5-3.0); in the second slurry, N2 is (1.0-1.2):1:(1.5-3.0). After a large number of experiments, the inventors adjusted and optimized the molar ratios of the P element, Fe element, and Li element in the two slurries, and finally obtained the above two ranges. The adjustment of the above molar ratio range is more conducive to the formation of lithium iron phosphate with larger primary particles in the slurry system with a low iron-phosphorus ratio, while the formation of lithium iron phosphate with smaller primary particles in the slurry system with a high iron-phosphorus ratio. In addition, the precursor particle size distribution provided by the two slurry systems is better matched to form a lithium iron phosphate positive electrode material with a more stable lattice structure and a more suitable particle size distribution, and ultimately improves the compaction density and discharge performance of the resulting material.

[0030] For the solvent system provided by the present invention, it is preferred that the weight ratio of water, ethylene glycol and organic acid in the first solvent and the second solvent is independently (1.0-2.0): (0.5-1.0): (1.0-3.0). The solvent prepared by mixing water, ethylene glycol and organic acid according to the above weight ratio can improve the rheological properties of the slurry while more significantly exerting the regulating and inducing effect of organic acid on the crystal structure, and promote the uniform dispersion and growth of the obtained positive electrode material particles, thereby obtaining a more compact lithium iron phosphate material with higher compaction density. In several typical embodiments, the organic acid is preferably selected from one or more of malonic acid, succinic acid, citric acid and oxalic acid. The above-mentioned types of organic acids can not only be used as inducers to optimize and regulate the crystal structure of lithium iron phosphate positive electrode materials, but also can be better compatible with P elements, Fe elements, and Li elements, and optimize the crystal growth rate and morphology during the reaction process, thereby obtaining lithium iron phosphate positive electrode materials with better electrochemical properties.

[0031] During the experiment, step S1 includes: preparing a first phosphorus source, a first iron source, a first carbon source and a first solvent into a first intermediate slurry, and then adding a first lithium source to the first intermediate slurry to obtain a first slurry; step S2 includes: preparing a second phosphorus source, a second iron source, a second carbon source and a second solvent into a second intermediate slurry, and then adding a second lithium source to the second intermediate slurry to obtain a second slurry. That is, in the preparation process of the two slurries, the lithium source is added to the slurry system after the other raw materials form a uniform intermediate slurry. This preparation method can improve the uniformity of the material and the consistency of the reaction, thereby enhancing the electrochemical performance of the positive electrode material, and ultimately making the obtained lithium iron phosphate positive electrode material have better cycle stability and higher energy density.

[0032] Furthermore, step S1 also includes adding a first pH adjusting agent to the first slurry so that the pH of the first slurry is 6.5 to 7.5 to obtain a first precursor; step S2 also includes adding a second pH adjusting agent to the second slurry so that the pH of the second slurry is 6.5 to 7.5 to obtain a second precursor. By adjusting the pH values ​​of the two slurries, the precipitation conditions of the precursors can be optimized, and two precursors with different particle size distributions can be obtained in advance, thereby more effectively optimizing the particle size distribution of the final lithium iron phosphate positive electrode material in the subsequent mixing and reaction process, improving the purity and crystallinity of the material, and making it exhibit higher electrochemical performance. On this basis, it is preferred that the first pH adjusting agent and the second pH adjusting agent are independently selected from one or more of hydrochloric acid, sulfuric acid, malonic acid, succinic acid, citric acid and oxalic acid. Theoretically, the first pH adjuster and the second pH adjuster can both be acids commonly used in the art. The selection of the above pH adjusters can not only effectively control the acidity and alkalinity of the first slurry and the second slurry, but also more effectively promote the formation of two precursors with different particle size distributions, thereby improving the electrochemical activity of the final positive electrode material.

[0033] In order to more effectively optimize the particle size distribution of the obtained lithium iron phosphate positive electrode material, the inventors, after a large number of experiments, preferably set the weight ratio of the first precursor in the first slurry to the second precursor in the second slurry in step S3 to (5-10): 1. This ratio control can better coordinate the two precursors with different particle sizes and distributions, improve the uniformity of the reaction process, better avoid crystal defects, and ultimately make the compaction density and discharge performance of the obtained lithium iron phosphate positive electrode material higher.

[0034] Further, the first carbon source is added in an amount of 0.5% to 1.5% based on the total weight of the first phosphorus source, the first iron source, the first carbon source and the first lithium source as 100%; and / or, the second carbon source is added in an amount of 0.5% to 1.5% based on the total weight of the second phosphorus source, the second iron source, the second carbon source and the second lithium source as 100%. The introduction of the above specific amount of carbon source can form a more uniform carbon coating layer, thereby further improving the conductivity of the obtained positive electrode material, reducing its internal resistance, and making it show a lower resistivity.

[0035] Furthermore, in order to promote the precursor generation reaction and the subsequent reaction of obtaining the positive electrode material to proceed more fully, while also improving the dispersion uniformity of the reaction system at each stage, and better reducing the adverse effects of solvent residue on material properties, it is preferred that the weight ratio of the total weight of the first phosphorus source, the first iron source, the first carbon source and the first lithium source to the first solvent is (10-20): (1-5); and / or, the weight ratio of the total weight of the second phosphorus source, the second iron source, the second carbon source and the second lithium source to the second solvent is (10-20): (1-5), thereby obtaining a lithium iron phosphate positive electrode material with higher electrical properties.

[0036] In several typical embodiments, the first phosphorus source and the second phosphorus source are independently selected from phytic acid, NH 4 H 2 PO 4 and phosphoric acid; and / or, the first iron source and the second iron source are each independently selected from FeSO 4 7H 2 O、FePO 4 and Fe 2 O 3 One or more of; and / or, the first lithium source and the second lithium source are each independently selected from LiOH·H 2 O. Li 2 CO 3 and CH 3 COOLi; and / or, the first carbon source and the second carbon source are independently selected from one or more of glucose, sucrose and polyethylene glycol. The selection of the above raw material types can not only meet the synthesis requirements of lithium iron phosphate positive electrode materials, but more importantly, it can more effectively promote the optimization of material particle size distribution according to the preparation method provided by the present invention, thereby improving its compaction density and discharge performance.

[0037] In the process of mixing the two slurries and finally reacting to obtain the positive electrode material, the inventors have optimized the reaction temperature to be 150°C to 300°C and the reaction time to be 2h to 6h after a large number of experiments, and under this condition, lithium iron phosphate with higher crystallinity, fewer defects, more stable structure and longer-range order is obtained, and its discharge performance is more superior. At the same time, the preferred drying temperature is 60°C to 120°C and the time is 10h to 24h. The control of such drying conditions can more effectively remove the residual moisture in the crystal structure of the obtained positive electrode material, and at the same time can more effectively protect the integrity, continuity and stability of the structure, so that it exhibits better electrochemical performance in lithium-ion batteries. It is more preferred that the drying is vacuum drying, so as to more thoroughly remove the moisture and volatile substances in the positive electrode material, improve its purity and service life.

[0038] The second aspect of the present invention provides a lithium iron phosphate positive electrode material, which is prepared by the above-mentioned preparation method of the lithium iron phosphate positive electrode material, and the compaction density of the lithium iron phosphate positive electrode material is 2.50g / cm 2 ~2.72g / cm 2 , the powder resistivity is 3.5Ω·cm~9.5Ω·cm. The positive electrode material prepared by the present invention has higher compaction density and lower resistivity, and the crystal structure has higher long-range order, higher structural stability and higher service life.

[0039] The third aspect of the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive current collector and a positive active layer disposed on at least one side of the positive current collector, wherein the positive active layer comprises the above-mentioned lithium iron phosphate positive electrode material. Since the above-mentioned lithium iron phosphate obtained by the present invention has a higher compaction density, a lower powder resistivity and a more stable and long-range ordered crystal structure, when it is used as a positive electrode material in a lithium-ion battery, the obtained lithium-ion battery also exhibits higher electrical performance accordingly.

[0040] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0041] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0042] Example 1

[0043] A method for preparing a lithium iron phosphate positive electrode material:

[0044] Step S1, weigh phosphoric acid and FeSO according to the molar ratio of P, Fe and Li being 0.9:1:1.5 4 7H 2 O、LiOH·H 2 O, glucose was weighed according to the ratio of carbon source to the total weight of phosphorus source, iron source, lithium source and carbon source of 0.5%, to obtain the first phosphorus source, the first iron source, the first lithium source and the first carbon source; the first solvent was prepared according to the mass ratio of water, ethylene glycol and citric acid of 1:0.5:1, and the first phosphorus source, the first iron source, the first carbon source and the first solvent were mixed and stirred for 1 hour according to the total weight of the first phosphorus source, the first iron source, the first lithium source and the first carbon source: the weight of the first solvent = 1:10 to obtain the first intermediate slurry; LiOH·H was slowly dripped into the first intermediate slurry 2 O, to obtain a first slurry; add hydrochloric acid to the first slurry, adjust the pH value to 6.5, and continue stirring for 30 minutes to react in the first slurry to generate a first precursor.

[0045] Step S2: weigh phosphoric acid and FeSO4 according to the molar ratio of P, Fe and Li being 1:1:1.5. 4 7H 2 O、LiOH·H 2 O, weighing glucose according to the ratio of carbon source to the total weight of phosphorus source, iron source, lithium source and carbon source of 0.5%, obtaining a second phosphorus source, a second iron source, a second lithium source and a second carbon source; preparing a second solvent according to the mass ratio of water, ethylene glycol and citric acid of 1:0.5:1, and mixing and stirring the second phosphorus source, the second iron source, the second carbon source and the second solvent for 1 hour according to the total weight of the second phosphorus source, the second iron source, the second lithium source and the second carbon source: the weight of the second solvent = 1:10, to obtain a second intermediate slurry; slowly dripping LiOH·H into the second intermediate slurry 2 O, to obtain a second slurry; add hydrochloric acid to the second slurry, adjust its pH value to 6.5, and continue stirring for 30 minutes to react in the second slurry to generate a second precursor.

[0046] Step S3, mixing the first slurry and the second slurry in a mass ratio of the first precursor: the second precursor = 5:1, and transferring the mixed third slurry to a reactor with a polytetrafluoroethylene lining for hydrothermal reaction, the temperature of the hydrothermal reaction is 150°C, and the time is 4 hours; after the reaction is completed, it is naturally cooled to room temperature, and the lithium iron phosphate positive electrode material is obtained by filtering, washing and drying, and the drying condition is vacuum drying at 60°C for 24 hours.

[0047] The obtained lithium iron phosphate cathode material was tested by Raman spectroscopy at different powers, and the results were Figure 1 and Figure 2 .in, Figure 1 Shows 0~2000cm-1 Raman spectrum curve in the range, Figure 2 It shows 920cm -1 ~980cm -1 Raman spectrum curve in the range.

[0048] Example 2

[0049] A method for preparing a lithium iron phosphate positive electrode material:

[0050] Step S1: weigh NH 4 H 2 PO 4 、FePO 4 , Li 2 CO 3 , weigh sucrose according to the ratio of carbon source to the total weight of phosphorus source, iron source, lithium source and carbon source of 0.8%, to obtain the first phosphorus source, the first iron source, the first lithium source and the first carbon source; prepare the first solvent according to the mass ratio of water, ethylene glycol and succinic acid of 1:0.8:1.5, and mix the first phosphorus source, the first iron source, the first carbon source and the first solvent according to the total weight of the first phosphorus source, the first iron source, the first lithium source and the first carbon source: the weight of the first solvent = 2:10 for 1 hour to obtain the first intermediate slurry; slowly drop Li 2 CO 3 , obtaining a first slurry; adding hydrochloric acid to the first slurry, adjusting its pH value to 7.0, and continuing stirring for 30 minutes to react in the first slurry to generate a first precursor.

[0051] Step S2: weigh NH 4 H 2 PO 4 、FePO 4 , Li 2 CO 3 , weigh sucrose according to the ratio of carbon source to the total weight of phosphorus source, iron source, lithium source and carbon source of 0.8%, obtain the second phosphorus source, the second iron source, the second lithium source and the second carbon source; prepare the second solvent according to the mass ratio of water, ethylene glycol and succinic acid of 1:0.8:1.5, and mix the second phosphorus source, the second iron source, the second carbon source and the second solvent according to the total weight of the second phosphorus source, the second iron source, the second lithium source and the second carbon source: the weight of the second solvent = 2:10 for 1 hour to obtain the second intermediate slurry; slowly drop Li into the second intermediate slurry; 2 CO 3 , obtaining a second slurry; adding hydrochloric acid to the second slurry, adjusting its pH value to 7.0, and continuing stirring for 30 minutes to react in the second slurry to generate a second precursor.

[0052] Step S3, mixing the first slurry and the second slurry in a mass ratio of the first precursor: the second precursor = 6:1, and transferring the mixed third slurry to a reactor with a polytetrafluoroethylene lining for hydrothermal reaction, the temperature of the hydrothermal reaction is 200°C, and the time is 5 hours; after the reaction is completed, it is naturally cooled to room temperature, and filtered, washed and dried to obtain a lithium iron phosphate positive electrode material, and the drying condition is vacuum drying at 80°C for 20 hours.

[0053] Example 3

[0054] A method for preparing a lithium iron phosphate positive electrode material:

[0055] Step S1, weigh phosphoric acid, Fe, and Li in a molar ratio of 0.96:1:2.5. 2 O 3 , CH 3 COOLi, according to the ratio of carbon source to the total weight of phosphorus source, iron source, lithium source and carbon source of 1.0%, polyethylene glycol PEG was weighed to obtain the first phosphorus source, the first iron source, the first lithium source and the first carbon source; the first solvent was prepared according to the mass ratio of water, ethylene glycol and malonic acid of 1.5:1:2, and the first phosphorus source, the first iron source, the first lithium source and the first carbon source were mixed and stirred for 1.5 hours according to the total weight of the first phosphorus source, the first iron source, the first lithium source and the first carbon source: the weight of the first solvent = 2:15, to obtain the first intermediate slurry; CH 3 COOLi, to obtain a first slurry; sulfuric acid was added to the first slurry to adjust its pH value to 7.5, and stirring was continued for 30 minutes to react in the first slurry to generate a first precursor.

[0056] Step S2, weigh phosphoric acid, Fe, and Li in a molar ratio of 1.02:1:2. 2 O 3 , CH 3 COOLi, according to the ratio of carbon source to the total weight of phosphorus source, iron source, lithium source and carbon source of 1.0%, polyethylene glycol PEG was weighed to obtain a second phosphorus source, a second iron source, a second lithium source and a second carbon source; a second solvent was prepared according to the mass ratio of water, ethylene glycol and malonic acid of 1.5:1:2, and the second phosphorus source, the second iron source, the second lithium source and the second carbon source were mixed and stirred for 1.5 hours according to the total weight of the second phosphorus source, the second iron source, the second lithium source and the second carbon source: the weight of the second solvent = 2:15, to obtain a second intermediate slurry; CH 3 COOLi, to obtain a second slurry; sulfuric acid was added to the second slurry to adjust its pH value to 7.5, and stirring was continued for 30 minutes to react in the second slurry to generate a second precursor.

[0057] Step S3, mixing the first slurry and the second slurry in a mass ratio of the first precursor: the second precursor = 8:1, and transferring the mixed third slurry to a reactor with a polytetrafluoroethylene lining for hydrothermal reaction, the temperature of the hydrothermal reaction is 250°C, and the time is 4 hours; after the reaction is completed, it is naturally cooled to room temperature, and filtered, washed and dried to obtain a lithium iron phosphate positive electrode material, and the drying conditions are vacuum drying at 120°C for 10 hours.

[0058] Example 4

[0059] A method for preparing a lithium iron phosphate positive electrode material:

[0060] Step S1, weigh phosphoric acid and FeSO4 according to the molar ratio of P, Fe and Li being 0.98:1:3. 4 7H 2 O. Li 2 CO 3 , weigh glucose to obtain a first phosphorus source, a first iron source, a first lithium source and a first carbon source according to a ratio of 1.3% of the total weight of the phosphorus source, the iron source, the lithium source and the carbon source; prepare a first solvent according to a mass ratio of water, ethylene glycol and oxalic acid of 2:1:1, and mix and stir the first phosphorus source, the first iron source, the first carbon source and the first solvent for 2 hours according to a ratio of the total weight of the first phosphorus source, the first iron source, the first lithium source and the first carbon source: the weight of the first solvent = 3:15 to obtain a first intermediate slurry; slowly drip Li 2 CO 3 , obtaining a first slurry; adding malonic acid to the first slurry, adjusting its pH value to 7.5, and continuing stirring for 30 minutes to react in the first slurry to generate a first precursor.

[0061] Step S2: weigh phosphoric acid and FeSO4 according to the molar ratio of P, Fe and Li being 1.1:1:3. 4 7H 2 O. Li 2 CO 3 , weigh glucose to obtain a second phosphorus source, a second iron source, a second lithium source and a second carbon source according to a ratio of 1.3% of the total weight of the phosphorus source, the iron source, the lithium source and the carbon source; prepare a second solvent according to a mass ratio of 2:1:1 of water, ethylene glycol and oxalic acid, and mix and stir the second phosphorus source, the second iron source, the second carbon source and the second solvent for 2 hours according to a ratio of the total weight of the second phosphorus source, the second iron source, the second lithium source and the second carbon source: the weight of the second solvent = 3:15 to obtain a second intermediate slurry; slowly drip Li 2 CO 3 , obtaining a second slurry; adding malonic acid to the second slurry, adjusting its pH value to 7.5, and continuing stirring for 30 minutes to react in the second slurry to generate a second precursor.

[0062] Step S3, according to the mass ratio of the first precursor: the second precursor = 9:1, the first slurry and the second slurry are mixed, and the third slurry obtained by the mixture is transferred to a reactor with a polytetrafluoroethylene lining for hydrothermal reaction, the temperature of the hydrothermal reaction is 300°C, and the time is 3 hours; after the reaction is completed, it is naturally cooled to room temperature, and the lithium iron phosphate positive electrode material is obtained by filtering, washing and drying, and the drying condition is vacuum drying at 120°C for 14 hours.

[0063] Example 5

[0064] A method for preparing a lithium iron phosphate positive electrode material:

[0065] Step S1, weigh phytic acid, FeSO4 and 1:1:3 according to the molar ratio of P, Fe and Li. 4 7H 2 O、LiOH·H 2 O, polyethylene glycol PEG is weighed according to the ratio of carbon source to the total weight of phosphorus source, iron source, lithium source and carbon source of 1.5%, to obtain a first phosphorus source, a first iron source, a first lithium source and a first carbon source; a first solvent is prepared according to the mass ratio of water, ethylene glycol and malonic acid of 2:1:3, and the first phosphorus source, the first iron source, the first lithium source and the first carbon source are mixed and stirred for 2 hours according to the total weight of the first phosphorus source, the first iron source, the first lithium source and the first carbon source: the weight of the first solvent = 5:20 to obtain a first intermediate slurry; LiOH·H is slowly dripped into the first intermediate slurry 2 O, to obtain a first slurry; add citric acid to the first slurry, adjust the pH value to 7.0, and continue stirring for 30 minutes to react in the first slurry to generate a first precursor.

[0066] Step S2: weigh phytic acid and FeSO4 according to the molar ratio of P, Fe and Li being 1.2:1:3. 4 7H 2 O、LiOH·H 2 O, polyethylene glycol PEG was weighed according to the ratio of carbon source to the total weight of phosphorus source, iron source, lithium source and carbon source of 1.5%, to obtain a second phosphorus source, a second iron source, a second lithium source and a second carbon source; a second solvent was prepared according to the mass ratio of water, ethylene glycol and malonic acid of 2:1:3, and the second phosphorus source, the second iron source, the second lithium source and the second carbon source were mixed and stirred for 2 hours according to the total weight of the second phosphorus source, the second iron source, the second lithium source and the second carbon source: the weight of the second solvent = 5:20 to obtain a second intermediate slurry; LiOH·H was slowly dripped into the second intermediate slurry 2 O, to obtain a second slurry; add citric acid to the second slurry, adjust its pH value to 7.0, and continue stirring for 30 minutes to react in the second slurry to generate a second precursor.

[0067] Step S3, mixing the first slurry and the second slurry in a mass ratio of the first precursor: the second precursor = 10:1, and transferring the mixed third slurry to a reactor with a polytetrafluoroethylene lining for hydrothermal reaction, the temperature of the hydrothermal reaction is 300°C, and the time is 2 hours; after the reaction is completed, it is naturally cooled to room temperature, and filtered, washed and dried to obtain a lithium iron phosphate positive electrode material, and the drying conditions are vacuum drying at 100°C for 16 hours.

[0068] Example 6

[0069] A method for preparing a lithium iron phosphate positive electrode material:

[0070] The only difference between this embodiment and embodiment 1 is that in step S1, the molar ratio of P, Fe and Li in the first slurry is changed to 0.8:1:1.2.

[0071] Example 7

[0072] A method for preparing a lithium iron phosphate positive electrode material:

[0073] The only difference between this embodiment and embodiment 1 is that in step S2, the molar ratio of P, Fe and Li in the second slurry is changed to 1.5:1:1.

[0074] Example 8

[0075] A method for preparing a lithium iron phosphate positive electrode material:

[0076] The only difference between this embodiment and embodiment 1 is that in step S1, the mass ratio of water, ethylene glycol and malonic acid in the first solvent is changed to 0.8:0.4:3.5.

[0077] Example 9

[0078] A method for preparing a lithium iron phosphate positive electrode material:

[0079] The only difference between this embodiment and embodiment 1 is that in step S2, the mass ratio of water, ethylene glycol and malonic acid in the second solvent is changed to 2.5:1.5:0.5.

[0080] Example 10

[0081] A method for preparing a lithium iron phosphate positive electrode material:

[0082] The only difference between this embodiment and embodiment 1 is that in step S1, the amount of the first carbon source added is changed to 0.3%, and the total weight of the first phosphorus source, the first iron source, the first lithium source and the first carbon source: the weight of the first solvent is changed to = 25:0.5; simultaneously in step S2, the amount of the second carbon source added is changed to 0.3%, and the total weight of the second phosphorus source, the second iron source, the second lithium source and the second carbon source: the weight of the second solvent is changed to = 25:0.5.

[0083] Embodiment 11

[0084] A method for preparing a lithium iron phosphate positive electrode material:

[0085] The only difference between this embodiment and embodiment 1 is that in step S1, the amount of the first carbon source added is changed to 1.8%, and the total weight of the first phosphorus source, the first iron source, the first lithium source and the first carbon source: the weight of the first solvent is changed to = 5:10; simultaneously in step S2, the amount of the second carbon source added is changed to 1.8%, and the total weight of the second phosphorus source, the second iron source, the second lithium source and the second carbon source: the weight of the second solvent is changed to = 5:10.

[0086] Example 12

[0087] A method for preparing a lithium iron phosphate positive electrode material:

[0088] The only difference between this embodiment and embodiment 1 is that in step S3, the mass ratio of the first precursor to the second precursor is changed to 4:1.

[0089] Embodiment 13

[0090] A method for preparing a lithium iron phosphate positive electrode material:

[0091] The only difference between this embodiment and Embodiment 1 is that in step S3, the mass ratio of the first precursor to the second precursor is changed to 12:1.

[0092] Embodiment 14

[0093] A method for preparing a lithium iron phosphate positive electrode material:

[0094] The only difference between this embodiment and embodiment 1 is that in step S3, the temperature of the hydrothermal reaction is changed to 120° C., and the time is changed to 8 h; and the drying condition is changed to vacuum drying at 140° C. for 8 h.

[0095] Embodiment 15

[0096] A method for preparing a lithium iron phosphate positive electrode material:

[0097] The only difference between this embodiment and embodiment 1 is that in step S3, the temperature of the hydrothermal reaction is changed to 350° C., and the time is changed to 1 h; and the drying condition is changed to vacuum drying at 50° C. for 30 h.

[0098] Example 16

[0099] A method for preparing a lithium iron phosphate positive electrode material:

[0100] The only difference between this embodiment and embodiment 1 is that in step S1 and step S2, the lithium source is not slowly added to the intermediate slurry, but is added to the solvent together with the phosphorus source, the iron source and the carbon source to form the first slurry and the second slurry respectively.

[0101] Comparative Example 1

[0102] A method for preparing a lithium iron phosphate positive electrode material:

[0103] The only difference between this comparative example and Example 1 is that the first solvent and the second solvent do not include an organic acid, but are changed to a mixed solvent prepared by mixing water and ethylene glycol in a mass ratio of 1.5:1.

[0104] The obtained lithium iron phosphate cathode material was tested by Raman spectroscopy at different powers, and the results were Figure 3 as well as Figure 4 .in, Figure 3 Shows 0~2000cm -1 Raman spectrum curve in the range, Figure 4 It shows 920cm -1 ~980cm -1 Raman spectrum curve in the range.

[0105] Comparative Example 2

[0106] A method for preparing a lithium iron phosphate positive electrode material:

[0107] The only difference between this comparative example and Example 1 is that step S2 and step S3 are not performed, and the first precursor obtained in step S1 is used as the lithium iron phosphate positive electrode material.

[0108] Comparative Example 3

[0109] A method for preparing a lithium iron phosphate positive electrode material:

[0110] The only difference between this comparative example and Example 1 is that in step S2, the molar ratio of P, Fe, and Li in the second slurry is changed to 0.9:1:1.5, which is equal to that in the first slurry.

[0111] Comparative Example 4

[0112] A method for preparing a lithium iron phosphate positive electrode material:

[0113] The only difference between this comparative example and Example 1 is that the organic acid citric acid used in the first solvent and the second solvent is replaced by hydrochloric acid.

[0114] Comparative Example 5

[0115] A method for preparing a lithium iron phosphate positive electrode material:

[0116] The only difference between this comparative example and Example 1 is that the first solvent and the second solvent do not include ethylene glycol, but are changed to a mixed solvent prepared by mixing water and citric acid in a mass ratio of 1:1.

[0117] Test Method

[0118] Compacted density: tested in accordance with GB / T 30835-2014 "Carbon composite lithium iron phosphate positive electrode materials for lithium-ion batteries".

[0119] Powder resistivity: tested by four-probe method.

[0120] Raman spectroscopy: (1) Place the obtained lithium iron phosphate cathode material powder on a clean glass sheet and press the powder to compact it; (2) Use Raman spectroscopy to select the corresponding test conditions for the sample to perform a surface scan test with a wave number range of 40 cm -1 ~2000cm -1 The scanning range is a rectangular area of ​​10μm~20μm×10μm~20μm, the laser wavelength is 532nm, and the output power is adjusted from small to large to 1mW~3mW, 4mW~7mW, 10mW~15mW, and 20mW~25mW using a power attenuator. Tests are performed to obtain data respectively; (3) the Raman imaging spectrum is processed and an intensity-wavenumber diagram is drawn.

[0121] Lithium-ion battery sample preparation and performance test: According to the mass ratio of lithium iron phosphate positive electrode material: super P: PVDF: NMP = 1: 0.2: 0.2: 1.5, the raw materials were mixed evenly in a slurry mixer to obtain a positive electrode mixed slurry, which was coated to prepare a positive electrode sheet. Artificial graphite was used as the negative electrode material, and a negative electrode sheet was prepared by coating. 6 / EC+DEC (volume ratio 1:1) as electrolyte and Celgard 2400 membrane as separator to prepare lithium ion battery samples. The first efficiency of each battery sample was tested at 25°C and 0.2C, and the discharge specific capacity at 1C was tested at 25°C.

[0122] The above test was performed on the lithium iron phosphate positive electrode materials obtained in each embodiment and comparative example, and the obtained results are shown in Table 1.

[0123] Table 1

[0124]

[0125]

[0126] From the above description, it can be seen that the lithium iron phosphate positive electrode materials provided in the embodiments of the present invention have excellent compaction density and lower powder resistivity, and the corresponding lithium ion battery exhibits good discharge capacity, which is significantly higher than the relevant performance of the lithium ion battery in each comparative example. Therefore, the positive electrode materials provided in the above embodiments of the present invention can significantly improve the rate performance of the battery and increase the energy density of the battery.

[0127] By performing Raman spectroscopy tests at different powers on Example 1 and Comparative Example 1, it can be seen that Figure 1 (Example 1) and Figure 2 (Comparative Example 1) In the figure, the characteristic peak PO4 of the lithium iron phosphate positive electrode material 3- The peak is located at 950cm -1 , low wave number band 210cm -1 and 280cm -1 The two strong peaks observed at are the α-Fe 2 O 3 Structural peak.

[0128] Depend on Figure 1 and Figure 2 The Raman peak intensity-wavenumber curve shows that high laser power has a significant effect on the low-wavelength band and 950cm -1 ~1050cm -1 The peak shape has a great influence, especially at 950cm -1 The characteristic peak PO4 3- The peaks will decompose at higher laser powers. Figure 1 and Figure 2 The same laser power has a significant difference in the decomposition degree of lithium iron phosphate obtained in Example 1 and Comparative Example 1. In Comparative Example 1, at a laser power of 10mW to 15mW, compared with a lower laser power of 1mW to 3mW, the peak of lithium iron phosphate can be observed to be significantly attenuated, especially its PO4 3- The characteristic peak occurred at 8cm -1 The displacement of Example 1 under the laser power of 10mW to 15mW has no significant change compared with the laser power of 1mW to 3mW, and its PO4 3- The displacement of the characteristic peak is only 5 cm -1 .

[0129] The difference in the above-mentioned peak intensity and peak position changes of the lithium iron phosphate positive electrode materials obtained in Example 1 and Comparative Example 1 under laser irradiation of different powers largely reflects the difference in thermal stability of the two lithium iron phosphate positive electrode materials obtained. For crystalline materials, when the temperature rises, the thermal vibration of atoms inside the crystal intensifies. This vibration will destroy the long-range order of the crystal, causing disorder of the crystal structure, and even melting or decomposition. The thermal stability of the crystal represents the ability to resist such thermal vibration damage to a certain extent. That is to say, compared with the lithium iron phosphate obtained in Comparative Example 1, the lithium iron phosphate obtained in Example 1 has a stronger interaction force between atoms in its olivine crystal structure and a stronger long-range order of the crystal, so it shows better stability under laser irradiation, and is less likely to undergo structural changes when used as a positive electrode material for lithium-ion batteries, thereby enabling the corresponding lithium-ion batteries to exhibit more superior electrical properties.

[0130] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: include: Step S1, preparing a first slurry by mixing a first phosphorus source, a first iron source, a first carbon source, a first lithium source and a first solvent; Step S2, preparing a second slurry by mixing a second phosphorus source, a second iron source, a second carbon source, a second lithium source and a second solvent; Step S3, mixing the first slurry and the second slurry to obtain a third slurry, and obtaining the lithium iron phosphate positive electrode material after the third slurry is reacted and dried; In the first slurry, the molar ratio of P element, Fe element and Li element is N1; in the second slurry, the molar ratio of P element, Fe element and Li element is N2; N1 is not equal to N2; The first solvent and the second solvent both include water, ethylene glycol and an organic acid.

2. The preparation method according to claim 1, characterized in that: In the first slurry, the N1 is (0.9-1.0):1:(1.5-3.0); In the second slurry, the N2 is (1.0-1.2):1:(1.5-3.0).

3. The preparation method according to claim 1 or 2, characterized in that: In the first solvent and the second solvent, the weight ratio of the water, the ethylene glycol and the organic acid is independently (1.0-2.0): (0.5-1.0): (1.0~3.0); Preferably, the organic acid is selected from one or more of malonic acid, succinic acid, citric acid and oxalic acid.

4. The preparation method according to any one of claims 1 to 3, characterized in that The step S1 further includes adding a first pH adjuster to the first slurry to adjust the pH of the first slurry to 6.5 to 7.5, thereby obtaining a first precursor; The step S2 further includes adding a second pH adjuster to the second slurry so that the pH of the second slurry is 6.5 to 7.5, thereby obtaining a second precursor; Preferably, the first pH adjuster and the second pH adjuster are independently selected from one or more of hydrochloric acid, sulfuric acid, malonic acid, succinic acid, citric acid and oxalic acid.

5. The preparation method according to claim 4, characterized in that: In step S3, the weight ratio of the first precursor in the first slurry to the second precursor in the second slurry is (5-10):

1.

6. The preparation method according to any one of claims 1 to 5, characterized in that Based on the total weight of the first phosphorus source, the first iron source, the first carbon source and the first lithium source as 100%, the addition amount of the first carbon source accounts for 0.5% to 1.5%; and / or, based on the total weight of the second phosphorus source, the second iron source, the second carbon source and the second lithium source as 100%, the addition amount of the second carbon source accounts for 0.5% to 1.5%; Preferably, the weight ratio of the total weight of the first phosphorus source, the first iron source, the first carbon source and the first lithium source to the first solvent is (10-20):(1-5); and / or the weight ratio of the total weight of the second phosphorus source, the second iron source, the second carbon source and the second lithium source to the second solvent is (10-20):(1-5).

7. The preparation method according to any one of claims 1 to 6, characterized in that The first phosphorus source and the second phosphorus source are independently selected from one or more of phytic acid, NH4H2PO4 and phosphoric acid; and / or, The first iron source and the second iron source are independently selected from one or more of FeSO4·7H2O, FePO4 and Fe2O3; and / or, The first lithium source and the second lithium source are independently selected from one or more of LiOH·H2O, Li2CO3 and CH3COOLi; and / or, The first carbon source and the second carbon source are each independently selected from one or more of glucose, sucrose and polyethylene glycol.

8. The preparation method according to any one of claims 1 to 7, characterized in that In step S3, The reaction temperature is 150°C to 300°C and the reaction time is 2h to 6h; The drying temperature is 60°C to 120°C and the drying time is 10h to 24h; Preferably, the drying is vacuum drying.

9. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the preparation method of the lithium iron phosphate positive electrode material according to any one of claims 1 to 8, and the compaction density of the lithium iron phosphate positive electrode material is 2.50 g / cm 2 ~2.72g / cm 2 , the powder resistivity is 3.5Ω·cm~9.5Ω·cm.

10. A lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive current collector and a positive active layer disposed on at least one side of the positive current collector, characterized in that: The positive electrode active layer includes the lithium iron phosphate positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Nanometer lithium iron phosphate as well as preparation method and application thereof

    CN103050696A

  • High-compaction lithium iron phosphate material and preparation method thereof

    CN111217347A

  • Preparation method of flaky lithium iron phosphate electrode material

    CN111777051A

  • Preparation method of lithium iron phosphate, positive active material, positive pole piece, battery and electric device

    CN117088352A

  • PROCESS FOR SYNTHESIS OF ELECTRO-ACTIVE CARBON COATED LiFePO4 IN THE REACTOR

    IN202241039085A